Strengthening resilience in the aftermath of adversity: evaluation of the group-based intervention Mind-Spring, a naturalistic mixed-methods study among refugee groups in the Netherlands - Nolan, Elizabeth; van der Aa, Niels; Groen, Simon; de la Rie, Simone (Frontiers in Psychology, 2025)
BackgroundRefugees often experience multiple traumatic events before and during forced migration, compounded by daily stressors in resettlement, which can erode resilience and increase the risk of serious mental disorders. Strengthening resilience in the aftermath of adversity may help prevent such outcomes. Mind-Spring (MS) is a low-threshold, group-based psychosocial intervention designed to enhance resilience and well-being. Intervention groups were organized by language, cultural background, and gender, and co-facilitated by a mental health professional and a peer educator with lived refugee experience, shared culture and language, and long-term settlement in the host country. This study assessed the feasibility of MS and its impact on four mental health domains among refugees and asylum seekers in the Netherlands presenting with early trauma-related symptoms.MethodsA convergent parallel mixed-methods study involved four MS groups with 37 participants (72.37% female; mean age 47.4 years, SD = 13.6). Feasibility was evaluated through attendance rates and thematic analysis of pre- and post-intervention interviews. Quantitative outcomes were measured using the Brief Resilience Scale-6 (resilience), WHO-5 Well-being Index (well-being), Cantril Ladder (life satisfaction), and Sense of Coherence-Kinderen (sense of coherence). Changes were analyzed using paired t-tests, reliable change indices, and multilevel modeling.ResultsHigh attendance and positive feedback indicated MS is both feasible and acceptable. Participants valued peer support, native-language delivery (Arabic, Dari, Tigrinya, Ukrainian), and the role of peer educators in fostering trust, engagement, and cultural relevance. The intervention’s adaptability and its potential to identify individuals needing additional care underscore its role as both a preventive and bridging approach. Topics considered most helpful included psychoeducation, coping with stress and emotions, and navigating cultural identity. Quantitative analyses revealed medium-to-large effects across domains, with particularly large gains in well-being (d = 1.22), and 62.5% demonstrating positive reliable change. Life satisfaction improved progressively during the program.ConclusionMS is a feasible, acceptable, and culturally meaningful intervention for resettling refugees, associated with improvements in resilience, well-being, life satisfaction, and sense of coherence. Despite limitations related to sample size and demographic skew, findings add to the evidence base for culturally adapted psychosocial interventions, supporting MS as a promising component within broader refugee integration and mental health services.